Investigation of Oxidative Status of the 2-Furan-2-yl-1H-Benzimidazole in Rats - Karatas, Fikret; Servi, Suleyman; Kara, Haki; Kiran, Tuba R.; Saydam, Sinan (Humana Press Inc, 2008)
We investigated the influence of 2-furan-2-yl-1H-benzimidazole regarding vitamins A, E, C, selenium (Se), malondialdehyde (MDA), and glutathione peroxidase (GSH-Px) levels on rats. 2-Furan-2-yl-1H-benzimidazole was given to rats by subcutaneous injection every other day for a total of 22 injections. At the end of the experiment, Se levels were determined by using a fluorimetric method. Serum levels of vitamins A, E, C, and malondialdehyde (MDA) were determined by high-performance liquid chromatography. Glutathione peroxidase (GSH-Px) levels of erythrocytes were spectrophotometrically determined. Our experimental results showed that vitamins A, E, C, and Se levels were found generally lower than the control groups, while serum MDA level and GSH-Px activity flexibly increased, which is dependent on injection days. The observed decreases in vitamins A, E, C, and Se levels in the blood might be causally related to the increased amount of free radicals that are generated with 2-furan-2-yl-1H-benzimidazole injection. However, further investigations are needed to clarify the significance of this observation in respect with the 2-furan-2-yl-1H-benzimidazole injection.
Keywords: Benzimidazole; Vitamins (A. E. and C); Se; MDA; GSH-Px; Rat